WATER EXTRACTION FROM AIR AS AN ALTERNATIVE WATER SOURCE IN SARAWAK, MALAYSIA - SZE YING, CHANG (Universiti Malaysia Sarawak, 2022)
Atmospheric water has high potential to be implemented in Malaysia because of the relatively high average humidity. In this project, passive desiccant method and active condensation method were studied. The passive desiccant method was done by using a flat plate collector with calcium chloride desiccant, while the active condensation method was tested using a solar powered split air conditioning system. Results obtained show that the passive desiccant water extraction is affected by sunlight intensity, desiccant concentration, bed temperature, cover temperature and orientation of the collector. The water productivity of the collector is directly proportional to sunlight intensity, desiccant concentration, and bed temperature. When the cover temperature is higher than the dewpoint, the water production rate drops as the condensation rate is affected. The water productivity is also higher when the collector faces towards the sun. The experiments show the potential of the passive desiccant method as the high relative humidity in Malaysia allows more atmospheric water to be absorbed. The water productivity of the active condensation method is higher and more stable compared to the passive method. For the active method, the water productivity of the system is not affected by the surrounding condition, like sunlight intensity and temperature. The effect of the relative humidity in the room to the water yield is only significant when the relative humidity is between 10% to 40%. The solar powered air conditioning system achieved an average water production rate of 2.142L/h in the experiment when the relative humidity was higher than 75%. Hence, the active condensation method is more feasible than the passive desiccant method to extract and supply atmospheric water as an alternative water source in Malaysia.